Visitors Experience and Non-Formal Science Learning (NFSL) Approaches in Malaysia - Kamsor, Norzilawati Md.; Ahmad, Jasmine; Awis, Mahadir Ladisma (International Journal of Psychosocial Rehabilitation, 2020)
This paper explores two issues, one, Non-Formal Science Learning (NFSL) approaches offered at the National Science Centre (NSC) through visitors’ service experience and its influences on services; and two, the various theories on non-formal learning and its applicability for conceptualizing the NFSL. The pre-interview was intended to clarify on the variables for conceptualizing the effectiveness of NFSL at the science centre. Fifteen (15) visitors were interviewed to examine the learning approaches that visitors appreciate (physical servicescape, social servicescape and service delivery) and how these lead to the effectiveness of the main services offered by the science centre. The preliminary survey reveals that 90% of the respondents felt that the physical servicescape of the premise affect mood during the visit and highlighted specific issues on the cleanliness, temperature, odours and functionality of a few equipment/ exhibits in the galleries that may turn off their mood during the visit. 80% of the respondents highlighted social servicescape was missing. The staff at the centre was hardly seen on the ground, and respondents added that the lack of help from the staff might influence their decision to revisit the science centre in the future. Service delivery was assessed on two factors, namely the parking facility and service speed. Though the respondents complained about the location of the parking area, the majority of them agreed that the service speed level was acceptable. 95% of the respondents admit learning at least one new thing about science, technology, and innovation (STI) during the visit. Overall, 70% of the respondents enjoyed their visit to the NSC. The Environmental Psychology Theory, Social Learning Theory and Experiential Learning Theory are potential theories in conceptualizing and understanding the visitor’s services experience to overcome issues on decreasing interest of the public in STI awareness programs and increase the STI popularization in the society.